L’Évaluation d’Impacts sur la Santé (EIS) : une démarche d’intégration des champs santé-environnement dans la voie du développement durable Application à un projet d’aménagement urbain : la halte ferroviaire de Pontchaillou à Rennes - Laurine Tollec; Anne Roué le Gall; Alain Jourdren; Frédéric Auffray; Françoise Jabot; Anne Vidy; Pascal Thébault; Pauline Mordelet; Jean-Luc Potelon; Jean Simos (Développement Durable et Territoires)
This article offers initial feedback from a field experience on the design and implementation of a Health Impact Assessment (HIA) approach in the context of an urban planning project. This approach aims at minimizing negative impacts and optimizing positive impacts of the project on the health and quality of life of populations. A methodology based on the design of a multi-criteria grid with several health determinants was developed and a list of recommendations was subsequently suggested to decision-makers. The strengths of such a participatory and approach integrating both environmental health and sustainable development are discussed and methodological recommendations are produced in order to facilitate future use of such an approach in similar contexts.